2016
DOI: 10.3390/w8090413
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Fee Policy Analysis: A Computable General Equilibrium (CGE) Model of Water Resources and Water Environments

Abstract: Abstract:To alleviate increasingly serious water pollution and shortages in developing countries, various kinds of policies have been implemented by local governments. It is vital to quantify and evaluate the performance and potential economic impacts of these policies. This study develops a Computable General Equilibrium (CGE) model to simulate the regional economic and environmental effects of discharge fees. Firstly, water resources and water environment factors are separated from the input and output sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…They suggested offering a tax break on energy-intensive, labor-intensive export industries, and implementing a carbon tax return for other industries Yang et al [17] used a CGE model to quantitatively simulate the impact of energy tax scenarios. They found that an energy tax can help to minimize the CO 2 and SO 2 emissions, with increasing marginal emissions reduction costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They suggested offering a tax break on energy-intensive, labor-intensive export industries, and implementing a carbon tax return for other industries Yang et al [17] used a CGE model to quantitatively simulate the impact of energy tax scenarios. They found that an energy tax can help to minimize the CO 2 and SO 2 emissions, with increasing marginal emissions reduction costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Before the 2015 reform that replaced resource fees with taxes, the discharge standards consisted of three categories: "Integrated Wastewater Discharge Standard (GB8978-1996)", "Discharge Standard of Pollutants for Municipal Wastewater Treatment Plant (GB18918-2002)", and discharge standards of industrial pollutants [30]. The pollution discharge fee is 0.7 yuan per unit of water pollution [1]. After the new regulations, the "pollutant discharge fee" will be abolished.…”
Section: Water Pollution Tax Scenariosmentioning
confidence: 99%
“…Population growth and rapid economic development in recent decades have dramatically aggravated water pollution and water withdrawal in China, while climate change is resulting in an increasingly uncertain water supply and places additional pressure on constrained freshwater resources [1][2][3]. Thus, a series of policies have been proposed by the Chinese government to address the challenges posed by water shortage and water quality degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A water pricing scheme for irrigation water in conditions of unmetered water use is the measure that Lika et al [19] evaluate with a principal-agent model. Fang et al [20] apply a computable general equilibrium model to quantify the performance and potential economic impacts of discharge tariffs, and Ahmad et al [21] study the limits of water pricing in a developing country metropolis. Finally, Montilla-López et al [22] review the worldwide use of water banks as a re-allocation mechanism of water rights.…”
Section: Economic Instrumentsmentioning
confidence: 99%